Primary splenic angiosarcoma – the same diagnosis yielding two different clinical pictures. case report - Kamocki, Zbigniew; Steward, Agnieszka; Zaręba, Konrad Piotr; Kukliński, Adam; Kędra, Boguław (Contemporary Oncology/Współczesna Onkologia, 2013)
Splenic angiosarcoma has been presented as an extremely rare malignant tumour. Amongst the rarest of all neoplasms, primary splenic angiosarcoma comprises 0.14–0.25 of all annually reported cases per one million persons Splenic angiosarcoma was first described in 1879 by T. Langerhans. The clinical symptoms and diagnostic values associated with splenic angiosarcoma are extremely variable. Nonetheless, majority of the patients (75%) complain of abdominal pain, and a quarter to one-third present with rupture of the involved organ. We hereby report our experience with two splenic angiosarcoma cases, which despite being similar in their diagnosis, nonetheless present with an entirely different clinical picture. Our first case, whereby the patient presented with a liver that was also affected by the angiosarcoma of the spleen. In the second case however, although the patient did show evidence of metastasis to the abdominal cavity as well as the liver, she also suffered from primary adenocarcinoma of the colon. To our knowledge, no previous article has made mention of primary splenic angiosarcoma existing independently of another primary neoplasm. Both may be found in common practice, and ought to be highlighted for their significance as such.